KONSTRUKSI MAKNA BAKUPUKUL MANYAPU BAGI MASYARAKAT MAMALA MALUKU - Sulaeman Sulaeman; Mahdi Malawat; Darma Darma (Universitas Andalas, 2019)
Bakupukul manyapu is a ritual whipping each other's limbs to hurt and bleed with healing oils Mamala as nonverbal communication. The purpose of this study is to find and explain the motives, meaning and experience of Mamala society do bakupukul manyapu ritual communication. The research method using the phenomenological method that focuses on the study of meaning bakupukul manyapu ritual communication the perspective Mamala community who experience it. The research uses a qualitative approach based on constructivist paradigm with the technique of collecting data through in-depth interviews, participatory observation, study, library and documentation with supporting data based on Phenomenology perspective, symbolic interaction and social construction theory. The subject is Mamala society the perpetrator bakupukul manyapu with the purposive sampling technique. The result that Mamala society the bakupukul manyapu have a motive